Upcycling EAF graphite electrode waste into graphene-oxide–doped PEDOT:PSS for inverted perovskite solar cells - Yus Rama Denny; Mohamad Fadli; Muhammad Iman Santoso; Sulaeman Deni Ramdani; Rafa Jafar; Meilani Meilani (Center of Biomass & Renewable Energy (CBIORE), 2026)
Poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is widely used as a hole-transport layer (HTL) in inverted perovskite solar cells (PSCs), but its acidity and moisture affinity can limit device performance. This study aimed to evaluate a circular-materials route by upcycling electric-arc-furnace (EAF) graphite-electrode waste into graphene oxide (GO) and applying GO-doped PEDOT:PSS as an HTL modifier, while identifying a practical low-temperature processing window for inverted PSCs under ambient conditions. Graphene oxide was synthesized from EAF graphite waste and dispersed in water (1 mg mL⁻¹), then blended with PEDOT:PSS at different loadings. Inverted PSCs with an ITO/GO-doped PEDOT:PSS/CH₃NH₃PbI₃₋ₓClₓ/PCBM/Ag architecture were fabricated in ambient laboratory air (25–27 °C; RH ≈ 40%) without a glovebox. The effects of GO loading and perovskite annealing temperature (70–130 °C) were evaluated using J–V measurements under AM1.5G illumination, supported by SEM and XRD analyses. Moderate GO addition was associated with improved film coverage and fewer pinholes, while XRD indicated better phase formation near 100 °C. In contrast, excessive annealing (≈130 °C) increased PbI₂ signatures and coincided with severe performance degradation. The optimum condition (600 µL GO per 1 mL PEDOT:PSS and 100 °C annealing) produced a champion power conversion efficiency of 0.80%, with VOC = 0.795 V, JSC = 3.48 mA cm⁻², and FF = 28.9%. Although the efficiency remained modest, the results demonstrated the feasibility of waste-derived GO as a functional PEDOT:PSS interfacial modifier and established a low-temperature processing window governing film integrity and degradation signatures in inverted PSCs, providing a basis for further optimization.